Ruthenium Carbonyl Compounds Containing Polypyridine Ligands as Catalysts in the Reaction of N-Benzylideneaniline Hydrogenation - Moya-Duran, S; Moya-Duran, S; Brown-Alvarez, K; Brown-Alvarez, K; Vidal-Palomo, M; Vidal-Palomo, M; Negrete-Vergara, C; Negrete-Vergara, C (2012)
The synthesis and characterization of ruthenium complexes containing polypyridine ligands: Ru(dppz)(PPh 3) 2Cl 2, Ru(bpy)(PPh 3) 2Cl 2, Ru(phen)(PPh 3) 2Cl 2, Ru(dppz-Cl)(PPh 3) 2Cl 2, Ru(phen)(CO) 2Cl 2, Ru(bpy)(CO) 2Cl 2 and Ru(dppz)(CO) 2Cl 2 (where dppz: dipyrido[3,2-a:2?,3?-c]phenazine, dppz-Cl: 10-chlororodypirido[3,2-a:2?,3?-c]phenazine, phen: 1,10-phenanthroline and bipy: 2,2?-bipyridine) are reported. The ruthenium complexes show high activity as catalysts in the hydrogenation reaction of N-benzylideneaniline and the hydrogen transfer reaction. The products of the catalysis were obtained with conversions between 21 and 91% after 2 h of reaction. The Ru(phen)(CO) 2Cl 2 complex was the catalyst that showed the highest conversion (91%) for the hydrogenation of N-benzylideneaniline. The complexes Ru(dppz)(PPh 3) 2Cl 2, Ru(bpy)(PPh 3) 2Cl 2 and Ru(dppz)(CO) 2Cl 2 showed 99% conversion in the hydrogen transfer reaction. © 2012 Elsevier B.V. All rights reserved.